Disparitas Level Berpikir Geometri Berdasarkan Teori Van Hiele pada Pemahaman Konsep Lingkaran Siswa SMP - Zhafira Salsabila; Reny Wahyuni; Salsabila Putri Lathifah; Depa Azarina; Lingga Novia Ayu Wangi; Putri Balqis Humairoh; Jaka Wijaya (Mandalika Mathematics and Educations Journal, 2026)
This study aims to analyze the disparity in geometry thinking levels of junior high school students on circle material based on Van Hiele’s theory. This research employed a descriptive qualitative approach involving 42 ninth-grade students of SMP Negeri 11 Lubuklinggau selected through random sampling. Data were collected through tests and informal interviews and analyzed using the interactive model of Miles and Huberman. The results indicate a marked disparity in students’ geometry thinking levels. Most students have not achieved mastery at Level 0 (Visualization) with 88.1% and Level 1 (Analysis) with 81.0%, as shown by their inability to identify elements of a circle visually. At Level 2 (Informal Deduction), 45.2% of students have not reached mastery, although some were able to apply concepts correctly. These findings suggest that students’ abilities are still dominated by instrumental understanding without adequate relational understanding. Furthermore, this study reveals the presence of epistemological learning obstacles, characterized by a leap in thinking without strong mastery of fundamental concepts.